Met belgerinkel naar de winkel - Geirnaerdt, Wim; Keytsman, Els; Vancompernolle, Mia (Brussel: BBL; Gent: Komimo; Brussel: UNIZO, 2002)
"redactie: Wim Geirnaerdt, Els Keytsman, Mia Vancompernolle, ... et al."